Exploring Higher Education Pathways for Coping With the Threat of COVID-19: Does Parental Academic Background Matter? - Möller, Julius; Thürmer, J. Lukas; Tulis, Maria; Reiss, Stefan; Jonas, Eva (Frontiers in Psychology, 2022)
First-generation students (FGS) are more likely to feel misplaced and struggle at university than students with university-educated parents (continuous-generation students; CGS). We assumed that the shutdowns during the Coronavirus-pandemic would particularly threaten FGS due to obstructed coping mechanisms. Specifically, FGS may show lower identification with the academic setting and lower perceived fairness of the university system (system justification). We investigated whether FGS and CGS used different defenses to cope with the shutdown threat in a large sample of German-speaking students (N = 848). Using Structural Equation Modeling, we found that for all students, independent of academic parental background, high levels of system justification were associated with perceiving the learning situation as less threatening, better coping with failure, and less helplessness. However, in comparison to CGS, FGS showed small but significant reductions in system justification and relied more on concrete personal relationships with other students as well as their academic identity to cope with the threatening situation. We discuss implications for helping FGS succeed at university.